Effect of the finite speed of light in ionization of extended molecular systems - I. A. Ivanov (Nature Portfolio, 2021)
Abstract We study propagation effects due to the finite speed of light in ionization of extended molecular systems. We present a general quantitative theory of these effects and show under which conditions such effects should appear. The finite speed of light propagation effects are encoded in the non-dipole terms of the time-dependent Shrödinger equation and display themselves in the photoelectron momentum distribution projected on the molecular axis. Our numerical modeling for the $$\hbox {H}_{2}^{+}$$ H 2 + molecular ion and the $$\hbox {Ne}_2$$ Ne 2 dimer shows that the finite light propagation time from one atomic center to another can be accurately determined in a table top laser experiment which is much more readily accessible than the ground breaking synchrotron measurement by Grundmann et al. (Science 370:339, 2020).